Female Authorship in English Language Literature: Mary Shelley and Frankenstein (Research, Society and Development, 2021)
This paper aims to present a discussion about the works of female authorship in the collection of PNLD Literary 2018 and propose an analysis of the work Frankenstein or the modern Prometheus (1818) by writer Mary Shelley, from the Portuguese edition by Zahar, published in 2017. In order to carry out this research it is intended, through the theoretical contribution of the Aesthetics of Reception, to observe the potential of the work for the construction of the aesthetic reader in the classroom and if the book has an emancipatory discourse, since, in 2018, it was incorporated into the catalog of PNLD - Literary, indicated for the high school grades. The choice of this text (SHELLEY, 2017) is justified because it is written by women, because it is considered a universal classic, because it is present in the PNLD Literary of 2018 and because its theme is current and relevant to students.